Collection strategies as an instrument to reduce delinquency in the company Martyni Campestre, Garzón, Colombia - Mauricio Martinez Fernandez, Fabian; Alejandra Collazos Vargas , Maria; Alejandra Castro Suarez, Diana (Seven Editora, 2023)
The general objective of the research was to propose collection strategies that allow reducing delinquency in the company Martyni Campestre, Garzón, Colombia. The non-experimental research design was used, since it did not perform any manipulation of the variables studied, likewise the research had a sample of 6 collaborators belonging to the area in charge of collections, who were evaluated through the application of surveys, with the purpose to collect information regarding the situation of the company. In this way, the results allowed us to conclude that the company Martyni Campestre, Garzón, Colombia does not have adequate collection strategies, as well as a lack of training for workers to carry out effective tasks regarding the collection of debts, making this lack of motivation both employees and customers, lead the company to face high levels of delinquency of its customers, consequently affecting the company’s profitability. DOI: 10.56238/pacfdnsv1-125